2018
DOI: 10.1038/s41598-018-29395-6
|View full text |Cite
|
Sign up to set email alerts
|

Landscape limits gene flow and drives population structure in Agassiz’s desert tortoise (Gopherus agassizii)

Abstract: Distance, environmental heterogeneity and local adaptation can strongly influence population structure and connectivity. Understanding how these factors shape the genomic landscape of threatened species is a major goal in conservation genomics and wildlife management. Herein, we use thousands (6,859) of single nucleotide polymorphism markers and spatial data from hundreds of individuals (n = 646) to re-evaluate the population structure of Agassiz’s desert tortoise (Gopherus agassizii). Analyses resolve from 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 91 publications
(146 reference statements)
1
30
0
Order By: Relevance
“…Dispersal is still poorly understood within the Gopherus genus, and we did not have any tortoises with GPS loggers make large dispersal movements during the study period. While populations of the Mojave desert tortoise were historically continuously distributed across suitable habitat in the Mojave and Colorado deserts [31,32], populations of the closely related Sonoran desert tortoise, Gopherus morafkai, are mostly confined to discrete foothill habitats [96,112,113]. Genetic analysis has shown that these patchy populations were historically connected by individuals dispersing through relatively unsuitable resident habitat in valleys; this behavior of dispersing through unsuitable resident habitat is not known in Mojave desert tortoise but could occur and play a role in maintaining genetic connectivity [108].…”
Section: Discussionmentioning
confidence: 99%
“…Dispersal is still poorly understood within the Gopherus genus, and we did not have any tortoises with GPS loggers make large dispersal movements during the study period. While populations of the Mojave desert tortoise were historically continuously distributed across suitable habitat in the Mojave and Colorado deserts [31,32], populations of the closely related Sonoran desert tortoise, Gopherus morafkai, are mostly confined to discrete foothill habitats [96,112,113]. Genetic analysis has shown that these patchy populations were historically connected by individuals dispersing through relatively unsuitable resident habitat in valleys; this behavior of dispersing through unsuitable resident habitat is not known in Mojave desert tortoise but could occur and play a role in maintaining genetic connectivity [108].…”
Section: Discussionmentioning
confidence: 99%
“…Fish and Wildlife Service 2011). A number of genetic connectivity studies have shed light on restricted gene flow due to the long-term limiting factors on dispersal (i.e., over multiple generations; Hagerty et al 2011, S anchez-Ram ırez et al 2018). Although the model we present here represents a first approximation of potential habitat connectivity for the Mojave desert tortoise, it does account for many of the underlying, contemporary drivers of movement and dispersal that are not reflected in existing models or maps.…”
Section: Discussionmentioning
confidence: 99%
“…, Sánchez‐Ramírez et al. ). However, genetic studies might not detect the effects of landscape fragmentation for many generations, which can amount to over a century for this long‐lived species (U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Although GUs have been defined for G. agassizii (Murphy et al 2007, Sánchez-Ramírez et al 2018, these studies did not include sampling from near the southwestern limits of the species range (e.g., populations surrounding the Coachella Valley; Berry and Murphy 2019). The low density or absence of tortoises in much of the area surrounding the Coachella Valley is due to the lack of suitable habitat in such low elevation areas (much of which is below sea level) and environmental conditions that are physiologically challenging for sustaining G. agassizii populations (reviewed by Ernst andLovich 2009, Berry andMurphy 2019).…”
Section: Introductionmentioning
confidence: 99%